Proses Pendampingan melalui Komunikasi Teurapetik sebagai Upaya Pemulihan Psikologis Korban Perkosaan - Soib Tiara; Mutia Rahmi Pratiwi (An-Nida : Jurnal Komunikasi Islam, 2018)
The amount of rape case in Indonesia is quiet high, then in the end it mostly cause the pregnancy. The decision of the rape victim to keep their pregnancy and nurture the baby becomes a very hard point, thus need private accompaniment. It is in line to what the Legal Resoure Center does for the gender equality and human rights (LRC-KJHAM) that creates working groups. The focus is on human rights, especially women and childrens. This research aims to describe the therapeutic communication steps that are conducted as the efforts of recovering the victim’s psychology. This research is a qualitative research and using the descriptive analysis method. The result shows that the companion employs five steps of therapeutic communication, such as Pre interaction step, Initiation step, Orientation step, Working step and Termination step. The companion does various strategies that are adjusted to the case’s condition and situation thus every steps of therapeutic are exceeded.